PERBANDINGAN MODEL PEMBELAJARAN TALKING STICK DAN NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR IPA SISWA DIKELAS VIII SMP KARTIKA I-4 - Mustika Piliang, Fenny (Jurnal Metabio, 2021)
This study aims to determine the differences in student learning outcomes using Talking Stick and NHT in class VIII of SMP Kartika I-4 Pematangsiantar on the Human Digestive System material in the 2020/2021 Academic Year. This study is a type of quasi-experimental research (Quasi Experiment) that is given different treatments in each class. Samples were taken using cluster random sampling technique, obtained class VIII-1 was used as experimental class I using the Talking Stick learning model with a total of 23 students, while class VIII-3 was used as experimental class II using the NHT learning model with a total of 23 students, research data analysis, finding the average value, standard deviation, homogeneity test, normality test and t test. From the results of the study, the average value in the experimental class I was 85 while the student learning outcomes in the experimental class II were 80. From the results of hypothesis testing using the t test, t count (3.63) was obtained > t table (2.00), thus the alternative hypothesis (Ha) was accepted and (Ho) was rejected, meaning there was a significant difference in student learning outcomes using Talking Stick and NHT on the Human Digestive System material for class VIII of SMP Kartika I-4 Pematangsiantar in the 2020/2021 Academic Year.